How secondary students develop the meaning of fractions? A hermeneutic phenomenological study - Muhamad Galang Isnawan; Didi Suryadi; Turmudi Turmudi (Beta: Jurnal Tadris Matematika, 2022)
[English]: Understanding various meanings of fractions is a foundation to learn related fractions topics. However, students are struggling with this essential topic. This hermeneutic phenomenological study aims to further investigate the meaning of fractions developed by secondary school students, the process of constructing the meaning using models, and factors that hinder the development of the meaning. It involved twenty-two students given fractions tasks, and some students of the different categories of mathematics ability were selected to be interviewed. A thematic analysis using NVivo-12 found that some students interpret fractions as a tool and integers. Most of the students in all categories tend to espouse fractions as ratio and quotient. However, they cannot use the models to represent the meanings. This study reveals that the students’ developed meanings of fractions are limited and different from what primary students have. In addition, there is an inconsistency between the espoused meanings and the use of models. The limitation and inconsistency are considered to be affected by teachers’ lack of content knowledge on the topic and less attention to using models in teaching fractions. This study implies that (mathematics) teachers education should pay more attention to the meaning of fractions and their related models in learning. [Bahasa]: Memahami makna pecahan merupakan dasar untuk mempelajari topik-topik terkait pecahan. Namun, siswa masih mengalami kesulitan dalam topik penting ini. Penelitian fenomenologi hermeneutika ini bertujuan untuk mengkaji lebih lanjut makna pecahan yang dibangun oleh siswa sekolah menengah, proses mengkonstruksi makna menggunakan berbagai model, dan faktor-faktor yang menghambat pengembangan makna pecahan. Penelitian ini melibatkan dua puluh dua siswa yang diberikan tugas matematika dan beberapa siswa dari berbagai kategori kemampuan matematika dipilih untuk diwawancarai. Analisis tematik menggunakan NVivo-12 menemukan bahwa beberapa siswa memaknai pecahan sebagai alat bantu dan bilangan bulat. Sebagian besar siswa pada semua kategori kemampuan matematika cenderung memaknai pecahan sebagai rasio dan hasil bagi. Namun, mereka tidak bisa menggunakan model untuk merepresentasikan makna pecahan tersebut. Penelitian ini menunjukkan bahwa makna pecahan yang dimiliki oleh siswa terbatas dan berbeda dari makna pecahan yang dimiliki siswa sekolah dasar. Selain itu, terdapat inkonsistensi antara makna pecahan yang diungkap siswa dengan penggunaan model. Keterbatasan dan inkonsistensi tersebut dianggap dipengaruhi oleh kurangnya pengetahuan konten guru tentang materi dan kurangnya penggunaan model dalam mengajar pecahan. Dalam hal ini, pendidikan guru (matematika) harus lebih memperhatikan makna pecahan dan penggunaan model pecahan dalam pembelajaran.